Jasser Auda's Maqāṣid al-Sharī’ah: Transforming Professional Zakat for People's Welfare - Huda, M Ikhwanul; Kaamilah, Ummi Fadliyati; El Hijri, Muhammad Faqihuddin (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
In the current era, professions are increasingly diverse and offer substantial incomes, especially in Indonesia. The Indonesian Ulema Council (MUI) responded to the problem by issuing MUI Fatwa No. 3 Year 2003, which addresses the obligation of paying zakat on professional income. This research aims to discuss the welfare and social justice efforts made by MUI, providing confirmation of the obligation to pay professional zakat. This research employs a normative juridical approach, focusing on statutory analysis. The data used are MUI Fatwa Number 3 Year 2003 and previous studies related to Maqāṣid al-Shari’ah, then were analyzed through Jasser Auda's Maqāṣid al-Shari’ah theory to explore the role of MUI in efforts to implement social welfare and justice in the implementation of zakat payments. The results show that Jasser Auda's Maqāṣid theory is relevant to professional zakat in the modern era, where its obligation is grounded in the stability of income. In the concept of Wholeness, professional zakat must be paid through an institution or directly to the recipient. Openness equates it with zakat on commerce according to the MUI fatwa, which emphasizes justice. Interrelatedness shows the role of professional zakat in education, while multidimensionality offers flexibility in its empowerment. Finally, Purposefulness emphasizes the purpose of zakat in religious and socio-economic aspects.